Malla Abdulla ALFarhadi and His Humanitarian Position - Shwan Faisal Hamad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
In the name of Allah, the most gracious, the most Merciful, and praise be to Allah, and our Prophet and our master Muhammed bin Abdullah. The holy Islam and he has brought the knowledge of this religion to all humanity and the nation of Islam through his companions and followers since the beginning and continued until the present day through the religious scholars that are the inheritors of the holy message of this religion. Mala Abdullah Farhadi is one of the Kurdish famous scholars who was born in 1918 in the village Lheban in Erbil district. Despite of the tough and difficult political and economic conditions and circumstances Mala Abdallah has been able to educate and develop his career and he became a well-trained, experienced and professional scholar in his own time. He was a religious, pious and a patriotic person. This paper intends to present the significance of the role and efforts of Mala Abdullah in the field of religious studies and his humanitarian position, as well as his service to his country and nation in different aspects of academic positions and society. Mala Abdullah passed away on 4th October 2010 in Erbil and left his family, friends and his scholars a great shock. May Allah bless him. Finally, this research intends to clarify and present the truth about the life and the scientific and academic efforts of one of many Kurdish scholars who devoted their labors in serving Islam and Shariah, thus, this research becomes a noticeable, prominent, and accessible work for other scholars and eager readers in the different cultural, academic institutions and universities. In the end, Praise be to Allah the Lord of the Worlds.